KEMAMPUAN PRIOR OPINION MEMODERASI PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, PERTUMBUHAN PERUSAHAAN DAN RASIO AKTIVITAS TERHADAP OPINI AUDIT GOING CONCERN - Utami, Made Ayu Jayanti Prita; Sari, Maria M. Ratna; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.07.TAHUN 2017, 2017)
This study aimed to get empirical evidence of prior opinions in its ability to moderate the effect of profitability, leverage, liquidity, company growth and activity ratios on going concern audit opinion. Going concern opinion is an audit opinion issued by the auditor to assess whether there is substantial doubt on the entity's ability to maintain its viability in a time period not exceeding one year from the date of the audit report. Several previous studies have shown inconsistent results relating to the effect of financial ratios in the administration of going concern audit opinion. The difference results of these studies can be completed through a contingency approach, in which variables prior opinion allegedly moderating influence of financial ratios such as profitability, leverage, liquidity, growth and activity ratios to administration going concern audit opinion. This study uses secondary data. The population in this research is manufacturing companies listed in Indonesia Stock Exchange 2010-2015 period. The number of samples in the study were 438 samples were selected by purposive sampling. Data analysis technique used is the logistic regression analysis. The results obtained are prior opinion moderates and weaken the influence of profitability which is proxied by ROA on giving going concern audit opinions, but prior opinion does not moderate and strengthening the influence of leverage on giving going concern audit opinion, and prior opinion does not moderate and weaken the influence of liquidity, the company's growth and activity ratio on going concern audit opinion.
Keywords: prior opinion, going concern audit opinion, profitability, leverage, liquidity, company growth, activity ratio